Pengalaman Penyintas Covid-19 dengan Sindrom Long Covid - Elzina Dina De Fretes; Isra Nur Utari S. Potabuga (Jurnal Keperawatan, 2023)
This research aims to explore the experiences of patients experiencing long covid syndrome. Qualitative research method using thematic analysis techniques. The results of this study showed that 5 Partisipants experienced changes in health with general symptoms of fatigue, loss of smell and taste, difficulty breathing, fast heartbeat, hormonal disorders and high anxiety, namely 2 people experienced mild symptoms, two people experienced moderate symptoms and 1 person experienced symptoms which is heavy, with a long Covid period of 1 month to 1 year 6 months. Partisipants with comorbid asthma and hypertension experienced a longer recovery. Further initiation at home by community health center officers, one of whom received a referral from outside the area. Recommendations and implications of the results require health monitoring and rehabilitation for complete recovery.